2008
DOI: 10.1590/s1516-35982008000800020
|View full text |Cite
|
Sign up to set email alerts
|

Exigências de energia para mantença e eficiência de utilização da energia metabolizável para mantença e ganho de peso de caprinos Moxotó

Abstract: RESUMO -Objetivou-se avaliar as exigências líquidas de energia para mantença e as eficiências de utilização da energia metabolizável (EUEM) para mantença (km) e ganho de peso (kf). Utilizaram-se 26 animais da raça Moxotó, machos não-castrados com peso vivo (PV) médio inicial de 15 kg e 7 a 8 meses de idade, alimentados com dieta contendo 2,6 Mcal de energia metabolizável. No início do experimento, seis animais foram abatidos e serviram como referência para estimativa da composição corporal e do peso de corpo v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
2
1
0
1
Order By: Relevance
“…Comparing the values, we can infer that the breed factor, as well as the castration of the Canindé goats studied, may have contributed to the requirement of NE m values lower than those reported in other studies. In research with Moxotó goats in the same weight range as this study, Alves et al (2008b) found an average value of net energy for maintenance of 55.11 kcal/kg EBW 0.75 , similar to that estimated for the Canindé kids in our study (52.64 kcal/kg EBW 0.75 ). It can be proposed that the NEm values of indigenous animals are inferior to those obtained in studies with exotic breeds such as Saanen and Boer, which are more specialized for the production of milk or meat.…”
Section: Energy Requirements For Maintenancesupporting
confidence: 88%
“…Comparing the values, we can infer that the breed factor, as well as the castration of the Canindé goats studied, may have contributed to the requirement of NE m values lower than those reported in other studies. In research with Moxotó goats in the same weight range as this study, Alves et al (2008b) found an average value of net energy for maintenance of 55.11 kcal/kg EBW 0.75 , similar to that estimated for the Canindé kids in our study (52.64 kcal/kg EBW 0.75 ). It can be proposed that the NEm values of indigenous animals are inferior to those obtained in studies with exotic breeds such as Saanen and Boer, which are more specialized for the production of milk or meat.…”
Section: Energy Requirements For Maintenancesupporting
confidence: 88%
“…Use efficiency of ME for gain (k g ) presented itself inversely proportional to the concentration of ME in the diet, ranging from 0.62 to 0.30 for diets containing 2.08 to 2.69 Mcal/kg DM, respectively (Table 3), a behavior also reported by Alves et al (2008) in studies with Moxotó goats.…”
Section: Resultssupporting
confidence: 57%
“…Several models predict animal response from feed, climate and animal inputs. Among them, the model Cornell Net Carbohydrate and Protein System -Sheep (CNCPS-S) (Cannas et al, 2004) and more recently, Small Ruminant Nutrition System (SRNS) (Tedeschi et al, 2010) stand out. The latter is a modification of CNCPS-S to include the latest information, in addition to a sub-model for nutrition of goats.…”
Section: Introductionmentioning
confidence: 99%
“…Esses resultados são similares aos encontrados por Santos et al (2001) que não observaram diferença na produção leiteira de vacas recebendo óleo de soja e Modesto et al (2002) que não encontraram diferença no ganho de peso de bezerros suplementados com óleo de soja. Possivelmente a maior quantidade de energia não influenciou no crescimento dos cabritos, porque esses já recebiam energia suficiente para seu pleno desenvolvimento, de acordo com resultados encontrados por Sahlu et al (2004) e Alves et al (2008). Porém, esses resultados são contrários aos encontrados por Sampelayo et al (2003), que descreveram maiores necessidades energéticas para cabritos e Mancio et al (2005) que ao adicionar óleo de soja na dieta de cabritos em crescimento, o consumo de concentrado aumentou, resultando em maior ganho de peso.…”
Section: Discussionunclassified